JOURNAL OF GOVERNMENT & POLITICS : United States Counterterrorism on ISIS - Anton Minardi (FISIPOL UMY, 2016)
The U.S. counter terrorism on ISIS had implemented with various strategies including degrading ISIS's capability, shaping global coalition to defeat ISIS, and using trained military armed men for Iraq army forces, Kurdi army, Arabian army, and moderate opposition groups to fight against Bassar.